2018
DOI: 10.1007/s00228-018-2498-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of aripiprazole for the treatment of schizophrenia: an overview of systematic reviews

Abstract: Aripiprazole exhibited efficacy similar to that of other antipsychotic drugs and a better safety profile than that of typical (i.e., less some extrapyramidal side effects) and atypical (i.e., less metabolic changes) antipsychotic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 42 publications
0
47
0
1
Order By: Relevance
“…Aripiprazole displays high affinity for serotonin 5-HT1A and 5-HT2A receptors and dopamine D2 and D3 receptors [ 223 ]. The drug is unlikely to cause weight gain, sedation, or other changes in metabolism [ 226 , 230 , 231 , 232 ]. A 52-week trial of 478 patients with schizophrenia found that intramuscular injections of aripiprazole every four weeks (fixed at either 441 mg or 882 mg) was well-tolerated, making it a suitable treatment for schizophrenia [ 233 ].…”
Section: Role Of Antipsychoticsmentioning
confidence: 99%
“…Aripiprazole displays high affinity for serotonin 5-HT1A and 5-HT2A receptors and dopamine D2 and D3 receptors [ 223 ]. The drug is unlikely to cause weight gain, sedation, or other changes in metabolism [ 226 , 230 , 231 , 232 ]. A 52-week trial of 478 patients with schizophrenia found that intramuscular injections of aripiprazole every four weeks (fixed at either 441 mg or 882 mg) was well-tolerated, making it a suitable treatment for schizophrenia [ 233 ].…”
Section: Role Of Antipsychoticsmentioning
confidence: 99%
“…Thus, drugs such as aripiprazole, which can modulate the dopaminergic system, might be beneficial for reducing craving, rewarding effects, and relapse [16]. These characteristics, together with its well-established efficacy for the treatment of schizophrenia, the lower risk of extrapyramidal side effects compared to first-generation antipsychotics, and the lower risk of metabolic side effects compared to most second-generation antipsychotics [17], make aripiprazole an attractive alternative for the treatment of patients with schizophrenia with coexisting SUDs. Evidence from randomized clinical trials and laboratory studies has suggested that oral aripiprazole could be efficacious for the management of alcohol [18,19] or cocaine dependence [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical application of aripiprazole includes also bipolar disorder, major depression, obsessive-compulsive disorder, and autism. Aripiprazole is characterized by efficacy similar to that of both typical and atypical antipsychotic drugs (except olanzapine and amisulpride) [ 112 ]. Aripiprazole resulted in considerably lower weight gain and lower changes in glucose and cholesterol levels in comparison to clozapine, risperidone, and olanzapine [ 112 ].…”
Section: Multi-target Compounds To Treat Schizophreniamentioning
confidence: 99%
“…Aripiprazole is characterized by efficacy similar to that of both typical and atypical antipsychotic drugs (except olanzapine and amisulpride) [ 112 ]. Aripiprazole resulted in considerably lower weight gain and lower changes in glucose and cholesterol levels in comparison to clozapine, risperidone, and olanzapine [ 112 ]. Moreover, aripiprazole led to weaker EPS, less use of antiparkinsonian drugs, and akathisia, in comparison to typical antipsychotic drugs and risperidone [ 112 ].…”
Section: Multi-target Compounds To Treat Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation